Improvements in High Resolution Laryngeal Magnetic Resonance Imaging for Preoperative Transoral Laser Microsurgery and Radiotherapy Considerations in Early Lesions - Ruytenberg, Thomas; Verbist, Berit M.; Vonk-Van Oosten, Jordi; Astreinidou, Eleftheria; Sjögren, Elisabeth V.; Webb, Andrew G. (Frontiers in Oncology, 2018)
As the benefits, limitations and contraindications of transoral laser microsurgery (TLM) in glottic carcinoma treatments become better defined, pre-treatment imaging has become more important to assess the case-specific suitability of TLM and to predict functional outcomes both for treatment consideration and patient counseling. Magnetic resonance imaging (MRI) is the preferred modality to image such laryngeal tumors, even though imaging the larynx using MRI can be difficult. The first challenge is that there are no commercial radiofrequency (RF) coils that are specifically designed for imaging the larynx, and performance in terms of coverage and signal-to-noise ratio (SNR) is compromised using general-purpose RF coils. Secondly, motion in the neck region induced by breathing, swallowing and vessel pulsation can induce severe image artefacts, sometimes rendering the images unusable. In this paper we design a dedicated RF coil array which allows high quality high resolution imaging of the larynx. In addition we show that introducing respiratory-triggered acquisition improves the diagnostic quality of the images by minimizing breathing and swallowing artefacts. Together, these developments enable robust, essentially artefact-free images of the full larynx with an isotropic resolution of 1 mm to be acquired within a few minutes.